Implikasi Penyitaan Barang-barang Milik Negara dan Konsekuensi Hukumnya - Mohammad Effendi (Unisia, 2007)
Legal problems related to confiscation process of state properties should become a com- mon concern, especially in the era of administrative court. Execution of administrative court decisions is commonly accompanied by an order to pay damages or compensation. Regarding public bodies, such as Central and Regional Governments, together with their staffs, provision of damages and compensation is allocated in the National and Regional Budgets. Therefore, its implementation is relatively easier, and its problem relates only with administrative matters, different from other public bodies, such as state owned com- panies that are also included in executive tasks. This article recommends that a more detail regulation be important in order to implement administrative court decisions easier. Keywords: confiscation, public bodies, administrative court, decision.